Science Technology Engineering And Mathematics (STEM) Teacher Readiness: A Professional Development Perspective (International Journal of Environmental Sciences, 2025)
The National Education Policy (NEP), 2020 recommends inculcating twenty-firstcentury skills among students through technology-driven innovative interdisciplinary teaching-learning strategies. A STEM-integrated approach may be adopted to fulfil these national educational goals, but a prior investigation into teachers’ readiness is imperative. An explanatory mixed method approach was used to collect responses to closed-ended survey questions from 117 STEM teachers from schools in India's capital region to assess three STEM education dimensions: students’ use of technology, innovative teachers’ instruction in science, and their attitudes towards twenty-firstcentury learning among their students. To better understand the teachers’ perspectives, focus group discussion revealed different comprehension of the survey responses and difficulties faced in enacting STEM classes. Thematic analysis of data provided input for further actions of teacher training and procuring digital infrastructural support to the educational institutes for a smoother implementation of the academic policy.